2021
DOI: 10.3389/fphys.2021.731523
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bone Metabolism Markers to Ice Swimming in Regular Practitioners

Abstract: Objective: Both exercise and cold exposure cause physiological stress and they often occur in combination. However, the effects of exercise during severe cold on variation in bone metabolism in humans have remained elusive. The aim of this study was to investigate the variations in circulating bone metabolism markers after ice swimming (IS).Methods: Eighty-seven women and men aged 42–84 years old were recruited to perform regular IS activities. Serum parathyroid hormone (PTH), total calcium (Ca2+), total phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…There is currently no plausible interpretation for this paradox. Nonetheless, the mechanisms underlying our finding that the suppression of sclerostin after IS may be related to the alterations in circulating hormone levels in cold exercise condition and/or increased renal elimination: 1) most evidence from both human and animal studies supports parathyroid hormone (PTH) is an important suppressor of sclerostin ( Drake and Khosla, 2017 ), and we previously discovered that PTH increased significantly after IS ( Mu et al, 2021 ), which is possibly related to sclerostin inhibition. However, when we analyzed the relationship between PTH rising and sclerostin falling in our study population, with no significant relationship identified (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently no plausible interpretation for this paradox. Nonetheless, the mechanisms underlying our finding that the suppression of sclerostin after IS may be related to the alterations in circulating hormone levels in cold exercise condition and/or increased renal elimination: 1) most evidence from both human and animal studies supports parathyroid hormone (PTH) is an important suppressor of sclerostin ( Drake and Khosla, 2017 ), and we previously discovered that PTH increased significantly after IS ( Mu et al, 2021 ), which is possibly related to sclerostin inhibition. However, when we analyzed the relationship between PTH rising and sclerostin falling in our study population, with no significant relationship identified (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the results of 56 participants were included in this report. This study's processes followed those described in our previous studies (Mu et al, 2020;Mu et al, 2021). The IS portion of this study was conducted at IS sites in Liaoyang (12 January 2019) and Shenyang (26 January 2019, and16 February 2019).…”
Section: Participants and Study Designmentioning
confidence: 96%
See 1 more Smart Citation